ISSN exercise & sports nutrition review update: Research & recommendations - Kerksick, C. M.; Wilborn, C. D.; Roberts, M. D.; Smith-Ryan, A.; Kleiner, S. M.; Jäger, R.; Collins, R.; Cooke, M.; Davis, J. N.; Galvan, E.; Greenwood, M.; Lowery, L. M.; et al. (Journal of the International Society of Sports Nutrition, 2018)
Background: Sports nutrition is a constantly evolving field with hundreds of research papers published annually. In the year 2017 alone, 2082 articles were published under the key words `sport nutrition`. Consequently, staying current with the relevant literature is often difficult. Methods: This paper is an ongoing update of the sports nutrition review article originally published as the lead paper to launch the Journal of the International Society of Sports Nutrition in 2004 and updated in 2010. It presents a well-referenced overview of the current state of the science related to optimization of training and performance enhancement through exercise training and nutrition. Notably, due to the accelerated pace and size at which the literature base in this research area grows, the topics discussed will focus on muscle hypertrophy and performance enhancement. As such, this paper provides an overview of: 1.) How ergogenic aids and dietary supplements are defined in terms of governmental regulation and oversight; 2.) How dietary supplements are legally regulated in the United States; 3.) How to evaluate the scientific merit of nutritional supplements; 4.) General nutritional strategies to optimize performance and enhance recovery; and, 5.) An overview of our current understanding of nutritional approaches to augment skeletal muscle hypertrophy and the potential ergogenic value of various dietary and supplemental approaches. Conclusions: This updated review is to provide ISSN members and individuals interested in sports nutrition with information that can be implemented in educational, research or practical settings and serve as a foundational basis for determining the efficacy and safety of many common sport nutrition products and their ingredients.